2011
DOI: 10.1007/s11103-011-9734-8
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting cDNA-AFLP profiles between crown and leaf tissues of cold-acclimated wheat plants indicate differing regulatory circuitries for low temperature tolerance

Abstract: Low-temperature (LT) tolerance in winter wheat (Triticum aestivum L.) is an economically important but complex trait. Four selected wheat genotypes, a winter hardy cultivar, Norstar, a tender spring cultivar, Manitou and two near-isogenic lines with Vrn-A1 (spring Norstar) and vrn-A1 (winter Manitou) alleles of Manitou and Norstar were cold-acclimated at 6°C and crown and leaf tissues were collected at 0, 2, 14, 21, 35, 42, 56 and 70 days of cold acclimation. cDNA-AFLP profiling was used to determine temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 98 publications
(123 reference statements)
0
11
0
Order By: Relevance
“…Although the leaves would have been a more convenient tissue to use, recent experiments have shown that the low-temperature response of the leaves to cold treatment is different from that of the crown at the molecular level [9,20-22]. In overwintering wheat, it is the crown that survives to reestablish the plant roots and leaves in spring following high stress winters when sub-lethal tissue damage has been incurred.…”
Section: Resultsmentioning
confidence: 99%
“…Although the leaves would have been a more convenient tissue to use, recent experiments have shown that the low-temperature response of the leaves to cold treatment is different from that of the crown at the molecular level [9,20-22]. In overwintering wheat, it is the crown that survives to reestablish the plant roots and leaves in spring following high stress winters when sub-lethal tissue damage has been incurred.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic variations in general result from alterations in gene activities; therefore, it is likely that the differentially expressed TDFs formed genetic variations causing natural phenotypic variations. Since genome or transcriptome data are not available for Physalis , cDNA-AFLP technology, which is an efficient method of global transcriptional analysis for any species without a reference transcriptome (Ganeshan et al ., 2011; Yu et al ., 2011; Yang et al , 2012), was exploited to search for genes causing natural variation in the observed organ size. The 263 cloned differentially expressed TDFs have complicated expression patterns and they encode regulatory factors, protein kinases, protein phosphatase, and various enzymes, which contribute to the complexity of the genetic basis for the different floral phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…From a gene expression perspective, it has been shown that cold acclimation is associated with the significant upregulation or downregulation of hundreds to thousands of wheat genes (Gulick et al 2005; Monroy et al 2007; Laudencia-Chingcuanco et al 2011; Ganeshan et al 2011; Winfield et al 2009, 2010). Additional genes respond when acclimated plants are exposed to freezing temperatures (Herman et al 2006; Skinner 2009, 2015), leading to greater tolerance of subsequent, potentially damaging freezing events (Herman et al 2006; Skinner and Bellinger 2010).…”
mentioning
confidence: 99%